Substrate Integrated Waveguide Bandpass Filter with Complementary Split Ring Resonator at 2.45 GHz - Dian Widi Astuti; Sis Yasin Darmanik; Muslim Muslim; Mudrik Alaydrus (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Interferences between two applications should be avoided by using a filter. At present, the miniaturized filter is one of the requirement besides good quality and low insertion loss. The sixteenth-mode substrate integrated waveguide (SMSIW) is proposed by using a complementary split-ring resonator (CSRR) to fulfill miniaturized of filter. The filter design used two of sixteenth-mode SIW (SMSIW) that reduced 15/16 of the circular regular SIW. The frequency center filter design is at 2.5 GHz. The simulation result shows insertion loss value at 0.2 dB and return loss value at 29 dB, while for the measurement result gives insertion loss value at 0.7 dB and return loss value at more than 15 dB. It shows the measurement results give good value with the simulation results.